INFLUENCE OF DIFFERENT NITROGEN LEVELS ON GROWTH AND YIELD OF DIFFERENT RICE CULTIVARS - D. SANJEEVA RAO and K. SUPRIYA, B. SRIKANTH, D. SUBRAHMANYAM, S. NARENDER REDDY, J. VEERENDRA, C.N. NEERAJA (The Journal of Research, PJTSAU, 2023)
A field experiment was conducted during three consecutive seasons (Kharif 2020, Rabi 2021 and Kharif 2021) at IIRRfarm, Rajendranagar, Hyderabad to study the effect of different nitrogen levels application on growth and development in rice. The experiment was laid out in split plot design with four nitrogen levels as main plots, fourteen varieties as sub plots and replicated thrice. Among the nitrogen treatments, application of 150 kg N ha-1 recorded highest plant height (103.5, 98.1 and 98.7 cm),number of tillers hill-1 (9.5, 10.0 and 7.9), LAI (5.29, 5.06 and 5.20), SPAD value (45.3, 44.4 and 43.6), grain yield (5.16, 5.22 and4.94 t/ha) and more number of days to panicle initiation (78, 79 and77 days), 50% anthesis(100, 103 and 98 days) and maturity(130, 130 and 128 days) whereas lowest plant height (86.1, 82.2 and 86.1 cm), number of tillers hill-1 (5.7, 6.6 and 5.7), LAI(2.41, 2.40 and 2.49), SPAD value (38.3, 37.6 and 36.4), grain yield (2.76, 2.89 and 2.78 t/ha) and less number of days to panicleinitiation (76, 77 and74 days), 50% anthesis (96, 98 and 93 days) and maturity (125, 125 and 125 days) was noticed in 0 kg N ha-1 in Kharif-2020, Rabi-2021 and Kharif-2021, respectively. Anjali and Heerarecorded mean minimum number of days for panicleinitiation, 50% anthesis and maturity whereas mean maximum number of days for panicle initiation, 50% anthesis and maturitywere taken by Birupa and Daya. MTU-1010 recorded highest mean grain yield (4.83, 4.78 and 4.78 t/ha) whereas lowest grain yieldwas noticed in N-22 (3.01, 2.90 and 2.40 t/ha) in Kharif-2020, Rabi-2021 and Kharif-2021, respectively.